Pengaruh Persepsi Harga dan Kualitas Produk terhadap Keputusan Pembelian Silverqueen dengan Brand Image sebagai Mediasi : (Studi Kasus Palangka Raya) - Rina Elvi Sutikno; Selviana Frastika; Nina Lastari; Putri Lastari; Veronica Riani Dewi; Desi Juniarti; Ulfa Sri Wahyuni (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to determine how the influence of Price Perception and Product Quality on SilverQueen Purchasing Decisions with Brand Image as a Mediator of Brand Image (Community Study in Palangka Raya City). The type of research used is quantitative research. This sample was selected with characteristics according to indicators and respondents totaling 100 samples. In this study, an outer model (convergent validity and decriminal validity) and an inner model using the SMARTPLS 4 application were used to process data.